E-COMMERCE IN BUSINESS DEVELOPMENT - BOKOVETS, V.; DAVYDYUK, L. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The globalization of the global market creates new opportunities to facilitate doing business online. Every day, more and more companies around the world are implementing e-commerce tools, which allows them to attract new customers and, consequently, increase profits. The sphere of trade relations, which is actively moving into the online world, is no exception. That is why the study of the current state of development of e-commerce is relevant.The article reveals the prerequisites for the development of e-commerce, explores the importance of business development through e-commerce. It is noted that the study of this topic is especially relevant because, one of the most significant changes that the world of business is currently experiencing is the progressive development and implementation of e-commerce. Given the rapid development of web and Internet technologies, e-commerce is growing worldwide and is emerging as a separate sector of the economy. The development of technology, the Internet and the globalization of this process have significantly affected international trade. The largest regions of e-commerce, companies selling e-commerce are analyzed; share of online orders in Ukraine.
Keywords: technologies; globalization; e-commerce; e-commerce; online